Oil Extraction and Gender Equality for Social Equity: The Role of Corporate Social Responsibility in Nigeria's Coastal Communities - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
We examine the impact of multinational oil companies' (MOCs) corporate social responsibility (CSR) on gender equality for social equity using a combined propensity score matching and logit model. The result indicates a significant relationship between CSR and gender equality for social equity in coastal communities of Nigeria's oil producing region. This implies that CSR of MOCs is a critical factor for promoting equal opportunity, equal access, equal treatment, equal sharing and division of resources. The finding suggest for improved CSR investment of MOCs on empowering the women in coastal communities in taking up alternative livelihoods from conservation and marine resources.
Keywords: 330; Oil extraction; Gender equality; Social equity; Corporate social responsibility; Coastal communities; sub-Saharan Africa